The Role of JICA in the Central Asia Plus Japan Framework as an Instrument of Japan’s Development Diplomacy in Central Asia - Putri, Zalika Gantina Kayla; A’yuni, Meita Qurrotu; Zannah, Aisyatuzzahra Raudhatul; Latumaerissa, Jessica Nyzileitha; Putri, Sylvia Octa; Primawanti, Henike (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Japan is attempting to increase its footprint in Central Asia despite the region’s enormous potential as a transcontinental passageway Central Asia Plus Japan Dialogue (CA+JAD) This study seeks to determine the strategic significance of the Japan as a tool for Japan’s development diplomacy in the area, the International Cooperation Agency (JICA) The qualitative method used combines semi-structured interviews with data synthesis from a literature review. Interviews with JICA volunteers. The results show that JICA is the main operator, converting diplomaticTechnical support, excellent infrastructure, and large human resources help to translate vision into tangible projects developing capacity during the official development assistance implementation. A short discussion shows that these Japan’s sustainable development is bridged by the efforts that establish long-term trust based on the local ownership concept agenda emphasizing regional stability in Central Asia. In essence, JICA is a powerful tool for diplomacy in a multipolar geopolitical setting. The results of this study support Japan’s status as a trustworthy country and flexible partner, offering thoughts for other players in development diplomacy, JICA, ODA, and regional Central Asian cooperation.